KONSTRUKSI MORALITAS BISNIS DALAM ISLAM PERSPEKTIF HADIS - Muhammad Hotibul Umam; Muhammad Alif (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2026)
Business activities in the modern economic landscape are often trapped in a capitalistic paradigm that justifies any means for profit accumulation, triggering various detrimental market distortions. This study aims to reconstruct the concept of business morality and business competition from an Islamic perspective through textual analysis of hadith. Using a qualitative method with a Grounded Theory approach, this study analyzes 16 selected ahkam hadiths from Kutubus Sittah through open coding, axial coding, and selective coding stages. The results found that the construction of Islamic business morality is built upon four integrated main dimensions: (1) Basic Philosophy emphasizing consensualism (antaradin) and economic independence; (2) Elimination of Market Distortion through strict prohibitions on hoarding (ihtikar), price manipulation (najasy), and supply chain intervention; (3) Integrity-Based Professionalism requiring absolute honesty, product transparency, and service excellence; and (4) Divine Accountability placing the business vision on afterlife salvation. This study concludes that business ethics in Islam is not merely a normative rule, but a manifestation of worship combining individual piety and social justice to achieve equitable welfare (falah).